The application of photodynamic therapy in plastic and reconstructive surgery - Wu, Min; Huang, Xiaoyu; Gao, Lu; Zhou, Guoyu; Xie, Feng (Frontiers in Chemistry, 2022)
Photodynamic therapy (PDT) is a modern clinical treatment paradigm with the advantages of high selectivity, non-invasiveness, rare side-effect, no obvious drug resistance and easy combination with other therapies. These features have endowed PDT with high focus and application prospects. Studies of photodynamic therapy have been expanded in a lot of biomedical and clinical fields, especially Plastic and Reconstructive Surgery (PRS) the author major in. In this review, we emphasize the mechanism and advances in PDT related to the PRS applications including benign pigmented lesions, vascular malformations, inflammatory lesions, tumor and others. Besides, combined with clinical data analysis, the limitation of PDT and current issues that need to be addressed in the field of PRS have also been discussed. At last, a comprehensive discussion and outlooking represent future progress of PDT in PRS.